2004
DOI: 10.1021/jf0496043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Amendments on the Retention and Mobility of Imazaquin in Soils

Abstract: The influence of two organic amendments consisting of an urban waste compost (SUW) and a commercial amendment from olive mill wastes (OW) was assessed on the sorption properties and leaching of the ionizable herbicide imazaquin on four soils with different physicochemical characteristics. A loamy sand soil (CR), a loam soil (P44), a silt loam soil (AL), and a clay soil (TM), with low-medium organic matter contents, were chosen. Sorption-desorption experiments were performed on the original soils and on a mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…This strong retention to organically amended soil greatly limits any leaching or surface run-off of these herbicides [22]. In practice the application of organic amendments for retarded movement of the herbicides is more effective in sandy soils because of their originally lower adsorptive surfaces [51].…”
Section: Changes In Quaternary Herbicides Adsorption After Waste Bentmentioning
confidence: 99%
“…This strong retention to organically amended soil greatly limits any leaching or surface run-off of these herbicides [22]. In practice the application of organic amendments for retarded movement of the herbicides is more effective in sandy soils because of their originally lower adsorptive surfaces [51].…”
Section: Changes In Quaternary Herbicides Adsorption After Waste Bentmentioning
confidence: 99%
“…With respect to bensulfuron desorption, the H coefficient was lowest in soil amended with olive cake, indicating that desorption was inversely related to adsorption (Mamy & Barriuso, 2007). The composition and higher content of the OC from olive cake could be responsible for the greater retention of bensulfuron in soil amended with this olive residue (Undabeytia et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…An important management strategy for reducing herbicide leaching is to modify soil sorption potential by incorporating organic amendments, because a strong correlation has been usually observed between soil organic carbon (OC) content and pesticide sorption (Rouchaud et al. , 1997; Undabeytia et al. , 2004; Rodríguez‐Rubio et al.…”
Section: Introductionmentioning
confidence: 99%
“…(Garcia and Takashima, 2003). So far, only one paper reported the effect of organic manure on imazaquin environmental behavior, which indicated that the two amendments affected sorption and leaching of imazaquin in soils (Undabeytia et al, 2004). However, no data are available on the effect of manure on imazaquin degradation in soils.…”
Section: Introductionmentioning
confidence: 99%